An overlook on the current registries for rare and complex connective tissue diseases and the future scenario of TogethERN ReCONNET - Bandeira, Matilde; Di Cianni, Federica; Marinello, Diana; Arnaud, Laurent; Cannizzo, Sara; Carta, Claudio; Cornet, Alain; Barril, Sara M.; Bulina, Inita; Ferraris, Alessandro; Fonseca, João; Gaglioti, Andrea; et al. (Frontiers in Medicine, 2022)
Background – Patient registries play a crucial role in supporting clinical practice, healthcare planning and medical research, offering a real-world picture on rare and complex connective tissue diseases (rCTDs). ERN ReCONNET launched the first European Registry Infrastructure with the aim to plan, upgrade and link registries for rCTDs, with the final goal to promote a harmonized data collection approach all over Europe for rCTDs. Methods – An online survey addressed to healthcare professionals and patients’ representatives active in the field of rCTDs was integrated by an extensive database search in order to build a mapping of existing registries for rCTDs. Findings - A total of 140 registries were found, 38 of which include multiple diseases. No disease-specific registry was identified for relapsing polychondritis, mixed connective tissue disease and undifferentiated connective tissue disease. Discussion – This overview on the existing registries for rCTDs provides a useful starting point to identify the gaps and the strengths of registries on the coverage of rCTDs, and to develop a common data set and data collection approach for the establishment of the TogethERN ReCONNET Infrastructure.